Las escuelas-taller y casas de oficios en el ámbito de las ciencias de la documentación. - Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2001)
The aim of Workshop Schools and Crafts Training Centres since their crea don in 1985 has been Lo promote empioyment among young people and to pro vide them with the skills necessary for differentjobs and crafts, thus helping them to obtain employment. Sorne of these programs are related to Documentation Sciences and include subjecís like Librarianship, Archive Techniques, Restora tion and Hinding of Documents, Cinematographic Documentation and Graphie Documentation. These programs try to filí in some of the gaps that, due lo lack of regulated education in these professional categories, usually appear in the training of Archive, Library and Documentation Centre assistants. Studenís who work hard gain work experience thanks to contracts with collaborating bodies and complete these courses with the professional category of assistant.
Keywords: Workshop Schools Crafts Training Centres; Documentation Sciences